Phenotypic and genotypic identification of lactic acid bacteria isolated from spontaneous fermentation of unripe var. agung semeru banana (Musa paradisiaca formatypica) - N Nurhayati; Betty Sri Laksmi Jenie; Harsi D Kusumaningrum; sri widowati (Jurnal ILMU DASAR, 2011)
Lactic acid bacteria (LAB) can be found on food products such as milk and meat products, cerealia, cassava, fruits or vegetable products. The objectives of this research were to identify phenotypic and genotypic of lactic acid bacteria isolated from spontaneous fermentation of unripe var agung semeru banana (Musa paradisiaca formatypica). Phenotypic identification was based on general morphology, physiological test, API and Biolog system. Genotypic identification used polymerase chain reaction (PCR) method and analyses of 16S rRNA sequence. The result showed that two groups of LAB (FSnh 1 and FSnh A isolate) can use glicerol, D-ribose, D- xylose, D-glucose, D-fructose, D-mannose, methyl α D-gluco pyranoside, N-acetyl glucosamine, esculin ferric citrate, salicin, D-celiobiose, D-saccharose, gentibiose and potassium gluconate as carbon source. Beside that FSnh 1 isolate used D-galactose, L-sorbose, L-rhamnose, and amygdalin, while FSnh A isolate used metil αD- glukopiranosa, arbutin, D-maltose, D-lactose, D-trehalose, D-turanose, and potassium 5-ketogluconate as carbon source. The genotypic identification showed that Lactobacillus sp associated with the spontaneous fermentation of var agung semeru banana were identified as Lactobacillus salivarus and Lactobacillus fructivorans.